The ghosts of Langley into the CIA's heart of darkness - Prados, John (The New Press, 2017)
"The Ghosts of Langley is a provocative and panoramic new history of the Central Intelligence Agency that relates the agency's current predicament to its founding and earlier years, telling the story of the agency through the eyes of key figures in CIA history, including some of its most troubling covert actions around the world. It reveals how the agency, over seven decades, has resisted government accountability, going rogue in a series of highly questionable ventures that reach their apotheosis with the secret overseas prisons and torture programs of the war on terror." -- from publisher's web site